The Role of the Banda Aceh City Manpower Office in Handling the Increase in the Number of Unemployed Due to Corona Virus Disease 2019 (Covid-19) - Armiwal, Armiwal; Thaib, Anwar; Banna, Wanda Alazri (Dinasti Publisher, 2023)
The problem of unemployment is still one of the main topics of discussion in Indonesia, especially during the COVID-19 pandemic and is one of the indicators that causes poverty in Indonesia in general and Banda Aceh City in particular. The absorption of labor which is still minimal will certainly cause low income of the community so that their purchasing power is also low, the purpose of this study is to see and obtain information about what efforts have been made by the Banda Aceh City Manpower Office in carrying out its role to deal with the unemployment rate in Banda Aceh City during the pandemic. Researchers want to see how the Banda Aceh City Manpower Office carries out its role to reduce the unemployment rate in Banda Aceh City during the pandemic. The research method used in this study is a qualitative descriptive research method. The descriptive method is a method used to examine the status of a group of people, an object, a condition, a system of thought, and a glimpse of events in the present. The results of this study indicate that the Banda Aceh City Manpower Office in carrying out its role to reduce the unemployment rate in Banda Aceh City by taking policies aimed at ensuring that programs/activities carried out in an effort to reduce unemployment can be implemented optimally. The many obstacles faced by the Banda Aceh City Manpower Office are in the areas of inadequate budget and Human Resources so that the implementation of programs/activities is hampered and delayed.